Op soek na die kontoere vir ’n teologies-etiese begronding van homoseksualiteit: ’n Gereformeerde perspektief - Compaan, Auke (Stellenbosch Theological Journal, 2016)
In search of the contours of theological ethics of human sexuality with regard to homosexuality: a Reformed perspective This article offers a description and discussion of the contours of theological ethics of human sexuality, with regard to homosexuality. In the first part of the article, the topic of homosexuality is discussed within the larger historical development of the concept of human nature in the broader tradition of the church. Here special attention is paid to the views of Philo of Alexandria, St. Augustine and St. Aquinas, showing that the right and wrong of the sexual act were judged in terms of the procreative potential of the act. In the second part of the article, I propose a reformed perspective with regard to sexual ethics. This is done by a re-reading of the concept of human nature, by removing it from the traditional Roman Catholic “nature-grace” paradigm of salvation and re-reading it in terms of the reformed paradigm of “creation (law)-sin-gospel”. I argue that behind this paradigm shift, there is a movement from an ontology of being to an ontology of relationality and that this implies a move from procreation as the foundation of sexual ethics to the seeking of erotic justice in all our intimate relationships as a basis for sexual ethics.